2014
DOI: 10.1016/j.immuni.2014.06.005
|View full text |Cite|
|
Sign up to set email alerts
|

Memory CD8+ T Cells Use Cell-Intrinsic Lipolysis to Support the Metabolic Programming Necessary for Development

Abstract: Summary Generation of CD8+ memory T (TM) cells requires metabolic reprogramming that is characterized by enhanced mitochondrial fatty acid oxidation (FAO). However, where the fatty acids (FA) that fuel this process come from remains unclear. We found that while CD8+ TM cells engaged higher levels of FAO, they acquired substantially fewer long-chain FA from their external environment than CD8+ effector T (TE) cells. Rather than using extracellular FA directly, TM cells used extracellular glucose to support FAO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
532
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(558 citation statements)
references
References 65 publications
21
532
4
1
Order By: Relevance
“…This concurrent flux through fatty acid synthesis and oxidation occurs normally in non-hepatic tissue as an adaptive mechanism to promote substrate utilization and increase cellular metabolic rate (Solinas et al 2004, Mottillo et al 2014, O'Sullivan et al 2014. Like in fatty liver, this simultaneous induction of lipogenesis and oxidation is proposed to be dependent upon diminished ACC2-generated malonyl-CoA and submaximal CPT1 inhibition (Yu et al 2002).…”
Section: The Interplay Of Dnl and Beta-oxidationmentioning
confidence: 99%
“…This concurrent flux through fatty acid synthesis and oxidation occurs normally in non-hepatic tissue as an adaptive mechanism to promote substrate utilization and increase cellular metabolic rate (Solinas et al 2004, Mottillo et al 2014, O'Sullivan et al 2014. Like in fatty liver, this simultaneous induction of lipogenesis and oxidation is proposed to be dependent upon diminished ACC2-generated malonyl-CoA and submaximal CPT1 inhibition (Yu et al 2002).…”
Section: The Interplay Of Dnl and Beta-oxidationmentioning
confidence: 99%
“…Contraction and memory formation sees a return to metabolic quiescence dominated by OXPHOS [6]. However, unlike naive T cells reliant on glucose, circulating memory T cells utilize endogenously synthesized fatty acids for OXPHOS [7,8]. The metabolic substrates used by T rm cells for OXPHOS were previously unknown.…”
mentioning
confidence: 99%
“…Exactly why cells respond to acetate in this way, however, remains unclear. It has been previously demonstrated that CD8 + memory T cells engage in a futile cycle of fatty acid synthesis and oxidation in order to support quiescence, as well as retain the ability to rapidly mount a reactivation response (O'Sullivan et al, 2014). Whether acetate exposure promotes this phenotype as another way to promote memory cell fate will be an interesting question for future study.…”
Section: Systemic Levels Of Acetate Increase In Response To Infectimentioning
confidence: 98%
“…Increased GAPDH activity might also contribute to enhanced glycolysis that accompanies T cell activation. Although ACSS1 and ACLY were implicated in the production of IFN-g, it is also possible that a second pool of acetate is activated in the cytosol by ACSS2, which could then be used to support fatty acid synthesis (FAS), as well as fatty acid oxidation (FAO), a mechanism that has also been shown to occur in memory T cells (O'Sullivan et al, 2014). CS, citrate synthase; PDH, pyruvate dehydrogenase; FAS, fatty acid synthesis; FAO, fatty acid oxidation; ACSS1, acetyl-CoA synthetase 1; ACSS2, acetyl-CoA synthetase 2; GAPDH, glycerol-3-phosphate dehydrogenase; IFN-g, interferon-g; ACLY, ATP-citrate lyase; OAA, oxaoloacetate.…”
Section: Systemic Levels Of Acetate Increase In Response To Infectimentioning
confidence: 99%